2021
DOI: 10.1089/ast.2020.2386
|View full text |Cite
|
Sign up to set email alerts
|

Earth-like Habitable Environments in the Subsurface of Mars

Abstract: In Earth's deep continental subsurface, where groundwaters are often isolated for >10 6 to 10 9 years, energy released by radionuclides within rock produces oxidants and reductants that drive metabolisms of nonphotosynthetic microorganisms. Similar processes could support past and present life in the martian subsurface. Sulfate-reducing microorganisms are common in Earth's deep subsurface, often using hydrogen derived directly from radiolysis of pore water and sulfate derived from oxidation of rock-matrix-host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 138 publications
(339 reference statements)
4
25
0
Order By: Relevance
“…Dzaugis et al (2018) showed that this fracture-based model yields radiolytic H2 production rates for Martian basaltic crust broadly comparable to those predicted for fine-grained Martian sediments by the model of Blair et al (2017). One implication of these studies, in agreement with other considerations, is that the best place to seek extant life on Mars today is probably the subsurface (e.g., Tarnas et al, 2021).…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Dzaugis et al (2018) showed that this fracture-based model yields radiolytic H2 production rates for Martian basaltic crust broadly comparable to those predicted for fine-grained Martian sediments by the model of Blair et al (2017). One implication of these studies, in agreement with other considerations, is that the best place to seek extant life on Mars today is probably the subsurface (e.g., Tarnas et al, 2021).…”
Section: Introductionsupporting
confidence: 83%
“…Assuming fully water-saturated basement, H2 production rates were found to be comparable to crystalline basement on Earth because of the higher porosity of Mars' crust, despite the lower concentrations of uranium and thorium. Updated (higher) radionuclide concentrations were used by Tarnas et al (2018Tarnas et al ( , 2021 to estimate an even greater rate of radiolytic H2 production on Mars, using the same model. Bouquet et al (2017) applied a similar model to Jupiter's moon, Europa.…”
Section: Introductionmentioning
confidence: 99%
“…(2007). One implication of these studies, in agreement with other considerations, is that the best place to seek extant life on Mars today is probably the subsurface (e.g., Tarnas et al., 2021).…”
Section: Introductionsupporting
confidence: 78%
“…Updated (higher) radionuclide concentrations were used by Tarnas et al. (2018, 2021) to estimate an even greater rate of radiolytic H 2 production on Mars, using the same model. Bouquet et al.…”
Section: Introductionmentioning
confidence: 99%
“…The findings of this study underscore the need to expand understanding of key radiogenic processes in the crust, both continental and marine, to validate quantitative models of fluid age and transport critical to understanding the degree of isolation, or degree of connection, of the subsurface to surface processes. Constraining radiogenic processes and their associated fluxes will provide refined habitability models of the subsurface, both for the Earth and on other solar system bodies, where habitability driven by radiolysis a major driver of current investigation 12,44,[50][51][52] .…”
Section: Discussionmentioning
confidence: 99%